Il placito (e i due diplomi) del diacono Gariberto - Ansani, Michele (Scrineum, 2021)
The paper aims to reconsider the chronological and contextual data of the ‘placitum’ taken in Piacenza with the deacon Gariberto as protagonist. This ’notitia iudicati’ was published first by Schiaparelli in 1903 and then again, obviously, in the Manaresi collection (on the date 880 December/881 February). It seems to exhibit for the first time the formulary of the ’ostensio cartae’. Armando Petrucci considered this placitum a forgery. This record contains the transcription of a diploma of Charles III (not otherwise preserved) for the deacon Gariberto: an interpolated text which explains and justifies the judicial occasion.